Gender Discrimination and Ancient Indian Texts (International Journal of Food and Nutritional Sciences, 2022)
This research paper delves into the intricate relationship between gender discrimination and ancient Indian texts. Throughout history, India's rich literary and religious traditions have played a pivotal role in shaping societal norms, including those related to gender roles and relations. This paper employs a comprehensive analysis of prominent ancient Indian texts, such as the Vedas, Upanishads, Manusmriti, Mahabharata, and Ramayana, to explore the portrayal of gender roles and discrimination within these literary and religious works.By examining the historical and cultural contexts in which these texts were composed, the study elucidates the intricate interplay between religion, philosophy, and societal expectations in influencing gender ideologies. Moreover, it evaluates the potential impacts of these ancient texts on the gender dynamics of their time and, by extension, on contemporary gender relations in India.